Dual drug delivery platforms for bone tissue engineering - V. K., Anupama Devi; Ray, Sarbajit; Arora, Udita; Mitra, Sunrito; Sionkowska, Alina; Jaiswal, Amit Kumar (Frontiers in Bioengineering and Biotechnology, 2022)
The dual delivery platforms used in bone tissue engineering provide supplementary bioactive compounds that include distinct medicines and growth factors thereby aiding enhanced bone regeneration. The delivery of these compounds can be adjusted for a short or prolonged time based on the requirement by altering various parameters of the carrier platform. The platforms thus used are fabricated to mimic the niche of the bone microenvironment, either in the form of porous 3D structure, microspheres, or films. Thus, this review article focuses on the concept of dual drug delivery platform and its importance, classification of various platforms for dual drug delivery specific to bone tissue engineering and finally highlights the foresight into the future direction of these techniques for better clinical applications.